Current therapeutic strategies for the management of intraoperative hypotension associated with the use of regional anesthesia in pregnant patients undergoing cesarean section. - Salamanca-Martínez, Isabella (2023)
This literature review aimed to determine effective therapeutic treatments as of 2022 to counteract the hypotensive effect caused by regional anesthesia in pregnant women undergoing cesarean section during intraoperative period. Currently, regional anesthesia is the method of choice for cesarean sections due to the safety it provides for both the mother and the fetus. Therefore, scientific evidence on the use of colloids, crystalloids, vasopressors, and physical measures to treat hypotension was analyzed. A literature search was conducted on the main databases, and 25 articles were reviewed. The results showed that arterial hypotension is the main complication of regional anesthesia, and the most appropriate treatment so far is a combination of different strategies such as volume management, use of vasopressors, and certain physical measures. It is also relevant to detect risk factors associated with hypotension in maternal evaluation during the pre-anesthetic assessment.